Silvanus Scott correspondence - Scott, Silvanus
Letter requesting volunteers for a military expedition near Providence, R.I.
British army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Great Britain. -- Army -- Colonial forces -- Rhode Island; Providence (R.I.) -- History -- Colonial period, ca. 1600-1775.; Rhode Island -- History -- Colonial period, ca. 1600-1775.; Army officers, British